2013
DOI: 10.1002/ett.2638
|View full text |Cite
|
Sign up to set email alerts
|

On the capacity of the cognitive interference channel with a common cognitive message

Abstract: In this paper the cognitive interference channel with a common message, a variation of the classical cognitive interference channel in which the cognitive message is decoded at both receivers, is studied. For this channel model new outer and inner bounds are developed as well as new capacity results for both the discrete memoryless and the Gaussian case. The outer bounds are derived using bounding techniques originally developed by Sato for the classical interference channel and Nair and El Gamal for the broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…In this case, we have r ′ 5 = 0 and r ′ 6 = 0 and r ′ 7 = r ′ 8 of the secondary receiver. We note that (a) the achievable rate region (the capacity) in (7), for the case of strong interference regime, and (b) the achievable rate region in (12), for the case of strong interference at only the primary destination, are equivalent. In particular, the decoding scheme and the achievable rate at the primary destination in the two cases are similar.…”
Section: Corollarymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, we have r ′ 5 = 0 and r ′ 6 = 0 and r ′ 7 = r ′ 8 of the secondary receiver. We note that (a) the achievable rate region (the capacity) in (7), for the case of strong interference regime, and (b) the achievable rate region in (12), for the case of strong interference at only the primary destination, are equivalent. In particular, the decoding scheme and the achievable rate at the primary destination in the two cases are similar.…”
Section: Corollarymentioning
confidence: 99%
“…In another encoding scheme, cognitive IC with transmitters cooperation were studied. [6][7][8] For example, a unidirectional cognitive link between the two transmitters is assumed. Then, the informed sender exploits interference cancellation scheme such as Gelfand and Pinsker (GP) technique to remove the effect of the other user's transmission at its receiver.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that some frequency bands are underused in a range from 15 to 85% [1][2][3][4][5]. Cognitive radio networks (CRN) allow a better use of frequency bands.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive radio has been recently proposed as a potential enabler to use efficiently the radio spectrum. Its idea is based on the dynamic spectrum access that allow unlicensed secondary users to access the spectrum opportunistically without adversely affecting the transmission performance of the license holders, called primary users. To share the spectrum in an opportunistic manner, two approaches have been proposed, namely underlay and overlay.…”
Section: Introductionmentioning
confidence: 99%